Poverty and Women Prostitution in Nigeria: A Study of Wukari Local Government Area, Taraba State - Ishaya, Samaila Atobauka; Ogunode Niyi Jacob (International Journal on Integrated Education, 2021)
Poverty and prostitution have plagued mankind since time immemorial and have equally engaged the fertile minds of scholars on how to mitigate their impacts on society. Wukari local government area and its environs have been affected by communal crisis of various types, resulting in the displacement of people and their means of livelihood. This has invariably increased poverty and prostitution. This study is therefore an attempt to examine the impact of poverty on women prostitution in Wukari Local Government Area of Taraba State. To achieve the objectives of this research, primary and secondary data and simple percentages were used in analyzing the data. The findings of the study showed that poverty is the major factor responsible for women prostitution in Nigeria and Wukari LGA in particular. This research also discussed the types of poverty and their impact in the Society, types of prostitution and the age bracket of the more vulnerable groups. This implies that government would spend more in curbing sexually transmitted diseases in the society, controlling abortions and preventing unwanted pregnancies and unwanted children. The study concluded by calling on government to create more job opportunities as a means of curtailing the existing high level of poverty in the society and to give equal employment opportunities to both sexes.